An Analysis of Islamic Law on the Factors of Breaking the Marriage Bond - Hasibuan, Nahar; Asridiyani, Asridiyani (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
This study aims to analyze the factors that cause the breakup of marriage ties in the perspective of Islamic law. The focus of this research is to examine the types of divorce regulated in Islamic jurisprudence, such as identifying internal and external factors that contribute to the breakup of marital relationships. This study uses a qualitative approach with descriptive analysis methods and literature studies. Primary data are drawn from classical and contemporary fiqh literature, while secondary data include jurisprudence studies, marriage laws in Muslim-majority countries, as well as previous research on the topic. The results of the study show that the factors that cause the breakup of marriage bonds in Islamic law include differences in principles between husband and wife, unresolved conflicts, domestic violence, and violations of marital obligations such as alimony or fidelity. External factors such as the influence of the modern social and cultural environment also play a role in increasing the divorce rate. From the perspective of Islamic law, the solution to overcome the breakdown of marriage lies in the emphasis on the mediation and deliberation process, as well as preventive efforts through pre-marital education. This study provides suggestions for future researchers to conduct a more in-depth analysis of the implementation of Islamic law in the context of divorce in countries with pluralistic legal systems